Effect of assessor's sex on visual color matching in dentistry: A systematic review of the literature - Hynková, Kristýna; Sarao, Simran Kaur; Voborná, Iva; Levin, Liran (Journal of esthetic and restorative dentistry, 2022)
OBJECTIVES: To evaluate systematically the influence of sex of dental professionals on their capability for visual color matching. MATERIALS AND METHODS: The protocol was registered on PROSPERO (CRD42020205393). PICOS question was develop based on the population, intervention, comparison, outcomes, and study design (PICOS). Eligibility criteria included cross section studies, randomized clinical trials and cohort studies that compared the effect of sex on the visual color matching process. Five electronic databases (Pubmed, Cochrane, EMBASE, Medline, and SCOPUS) and additional literature were screened independently by two researchers in July 2020. Clinical studies evaluating visual color matching skills of dental professionals were included. Studies that did not compare the difference between sexes were excluded. Duplicate articles were removed, titles and abstracts were screened, and studies were selected according to the inclusion criteria. Data were collected and reported in accordance with PRISMA guidelines. Risk of bias was assessed using Joanna Briggs Institute Critical Appraisal Tools. RESULTS: A total of 1192 articles were screened from which 132 full text articles were analyzed and 37 finally included in the systematic review. Most of the studies evaluated the color matching abilities of dental students in vitro with shade tabs or extracted teeth. Out of the 37 articles included, 25 reported no significant difference in shade matching abilities between the sexes. Of the 12 studies that found a significant difference, 11 reported that females had better scores in shade matching exercises. For all studies a low risk of bias was revealed for most of the domains. CONCLUSIONS: While the non-homogeneity of the settings and methods in the included studies make it impossible to construct aggregate statistic, this systematic review suggests that the sex is unlikely to be a critical factor influencing color matching abilities. CLINICAL SIGNIFICANCE: This study suggest that sex of dental professionals does not play a critical factor in matching satisfactory color of future dental restoration with surrounding teeth.
Keywords: Color Perception; visual; Prosthesis Coloring; Dental Prosthesis Design; Color; ženské pohlaví; zuby; Tooth; Humans; zubní protéza - design; color matching; sex; Female; shade matching; barva; barvení protéz; lidé; vnímání barev